Jae Lee's Hellshock - Lee, Jae 1972- (Image Comics, 2006)
In the confines of a psychiatric hospital, a suicidal young woman meets an enigmatic stranger who believes he is an angelic presence not of this earth gifted with the powers of God. Is she being seduced into a cult... or is she bearing witness to a miracle?